Violent groups and police tactics : should tear gas make crime preventers cry? - Panu Poutvaara; Mikael Priks (Center for Economic Studies and ifo Institute (CESifo), 2005)
Democratic societies are challenged by various violent and organized groups, be they terrorists, gangs or organized hooligans. In exchange for offering an identity, leaders in such groups typically require members to be violent. We introduce a simple model to capture these stylized facts, and then study the effects of policing. We find that an increase in the marginal cost of violence always reduces violence, while increasing the indiscriminate fixed cost may backfire and result in smaller and more violent groups.
Keywords: D74; D71; 330; violence; terrorism; gangs; hooliganism; supporter clubs; Gewalt; Soziale Gruppe; Kriminalpolitik; Kriminalitätsökonomik; Theorie; Hooliganism